THU0413 Normalisation of nailfold microvasculature after hematopoietic stem cell transplantation in severe systemic sclerosis. (12th June 2018) - Boonstra, M.; Noordhoek, D.C.; Beaart-van de Voorde, L.J.; Huizinga, T.W.; de Vries-Bouwstra, J.K.
Abstract : Background: Microangiopathy in Systemic Sclerosis (SSc), as visualised by nailfold capillary microscopy (NCM), is a dynamic and sequential process. Uncontrolled case-reports and a case-series report possible improvement of nailfold microangiopathy after hematopoietic stem cell transplantation (HSCT). Objectives: To evaluate differences in nailfold microvasculature in patients with severe SSc treated with HSCT and those treated otherwise. Methods: Severe SSc was defined as fulfilling criteria of the ASTIS trial. 1 For included patients two treatment groups were defined: 1. Patients treated with HSCT, 2. Patients treated otherwise (including cyclophosphamide, methotrexate, mycophenolate mofetil and rituximab). All available capillaroscopy images collected prior to and after treatment were scored independently by two trained observers, blinded for treatment. Scoring included categorical scores (0=no changes to 3≥66% alterations per millimetre) for capillary loss, neoangiogenesis, haemorrhages, dilatations, giants, disorganisation, together with a qualitative pattern and a VAS score for overall severity of microangiopathy. Results: In total 55 patients were included, of whom 33 were female, mean age was 50±13 years and median mRSS of 20. 15–28 Twenty-nine patients were treated with HSCT. After treatment categorical score of capillary loss was lower with HSCT (median score 1.0 vs. 2.0, p=0.04) and VAS scores for severity of microangiopathy were better with HSCT (50.0 vs. 67.3, p=0.03). Compared to controls, a typical SSc pattern was less frequent in patients treated with HSCT (n=12/22, 55%, vs. n=18/20, 90%p=0.01). In 25 patients (HSCT n=11, control n=14) images prior to treatment were available. Improvement in capillary loss (HSCT −0.5 [IQR −1 to 0] vs. control +0.3 [IQR −1.0 to 1.0] p=0.01;), dilatation (HSCT −1.5[IQR −2.0 to −1.0] vs. control 0.0 [IQR −1.0 to 0.5] p≤0.01) and VAS scores (HSCT median −32.5 [IQR −80.5 to −4.5] vs. - controls+2.0 [IQR −35.5 to +46.0] p≤0.01;) improved significantly more in the HSCT group. Conclusions: In patients with severe SSc, microangiopathy as reflected by nailfold capillaroscopy images, is less severe after treatment with HSCT and shows more improvement over time compared to patients with severe SSc treated otherwise. In specific, improvement seems to be characterised by normalisation of the capillary diameter and capillary density. To our knowledge, this is the first study to report on changes in microangiopathy after HSCT in a controlled study design. Reference: [1] van Laar JM, Farge D, Sont JK, Naraghi K, Marjanovic Z, Larghero J, et al. Autologous hematopoietic stem cell transplantation vs intravenous pulse cyclophosphamide in diffuse cutaneous systemic sclerosis: a randomized clinical trial. JAMA2014;311(24):2490–8. Disclosure of Interest: None declared